Pelaksanaan Bimbingan Konseling Dalam Membentuk Kecerdasan Spiritual Siswa - Afif Alfiyanto; Ibrahim Ibrahim; Ayu Mustika; Leny Marlina (Edumaspul: Jurnal Pendidikan, 2022)
This research is entitled “Implementation of counseling guidance in shaping student’s spiritual intelligence at MAN 3 Palembang”. The purpose of this research is to analyze the implementation of counseling guidance in shaping students’ spiritual intelligence at MAN 3 Palembang and to analyze the factors supporting and inhibiting. This research is a qualitative descriptive study. The main informant in this research is the coordinator of counseling guidance. While the supporting informants are school principals and BK teachers. Data collection techniques used are observation, interviews, and documentation. The data obtained were then analyzed descriptively using data analysis techniques, data presentation, conclusion drawing, and data validity. The results of the study indicate that the implementation of counseling guidance in shaping students’ spiritual intelligence at MAN 3 Palembang has been carried out well. The implementation of counseling guidance in shaping students’ spiritual intelligence is carried out by approaching students and carried out by carrying out motivation, coordination, and direction. At this implementation stage, it goes well by the goals and objectives so that it can form spiritual intelligence in students. As for the supporting factors, there is the cohesiveness of the counseling guidance team, facilities, and infrastructure to support counseling guidance in forming students’ spiritual intelligence and cooperative students. While the findings of the inhibiting factors in this study, namely, coming from the students themselves can be described, namely, themselves (individuals), family, association, and environment, as well as time limitations in implementing counseling guidance in shaping students’ spiritual intelligence. The implementation of counseling guidance in shaping students’ spiritual intelligence at MAN 3 Palembang has gone quite well but must still be considered and improved again to form students' spiritual intelligence properly.